![image](https://tex.z-dn.net/?f=y%3Dlog_%7B3%7D%28x%28x-3%29%29-log_%7B3%7Dx%5C%5C%0Ay%3Dlog_%7B3%7D%28%5Cfrac%7Bx%28x-3%29%7D%7Bx%7D%29%5C%5C%0Ay%3Dlog_%7B3%7D%28x-3%29%5C%5C%0Ax-3%3E0%5C%5C%0Ax%3E3%5C%5C%0A%283%3B%2Boo%29%5C%5C%0A)
0\\
x>3\\
(3;+oo)\\
" alt="y=log_{3}(x(x-3))-log_{3}x\\
y=log_{3}(\frac{x(x-3)}{x})\\
y=log_{3}(x-3)\\
x-3>0\\
x>3\\
(3;+oo)\\
" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=5%5E%7B%5Cfrac%7B1%7D%7Bx%7D%7D%2B5%5E%7B%5Cfrac%7B1%7D%7Bx%7D%2B2%7D%3E130%5C%5C%0A5%5E%7B%5Cfrac%7B1%7D%7Bx%7D%7D%2B5%5E%7B%5Cfrac%7B1%7D%7Bx%7D%7D%2A25%3E130%5C%5C%0A26%2A5%5E%7B%5Cfrac%7B1%7D%7Bx%7D%7D%3E130%5C%5C%0A5%5E%7B%5Cfrac%7B1%7D%7Bx%7D%7D%3E5%5C%5C%0A%5Cfrac%7B1%7D%7Bx%7D%3E1%5C%5C%0Ax%3E1%5C%5C%0A)
130\\
5^{\frac{1}{x}}+5^{\frac{1}{x}}*25>130\\
26*5^{\frac{1}{x}}>130\\
5^{\frac{1}{x}}>5\\
\frac{1}{x}>1\\
x>1\\
" alt="5^{\frac{1}{x}}+5^{\frac{1}{x}+2}>130\\
5^{\frac{1}{x}}+5^{\frac{1}{x}}*25>130\\
26*5^{\frac{1}{x}}>130\\
5^{\frac{1}{x}}>5\\
\frac{1}{x}>1\\
x>1\\
" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=y%3D%5Cfrac%7Bln%287-x%5E2%29%7D%7Bx%2B1%7D%5C%5C%0A%5C%5C%0Ax%2B1%3E0%5C%5C%0Ax%3E-1%5C%5C%0A7-x%5E2%3E0%5C%5C%0A-x%5E2%3E-7%5C%5C%0Ax%5E2%3C7%5C%5C%0A%28-1%3B%5Csqrt%7B7%7D%29%5C%5C%0A)
0\\
x>-1\\
7-x^2>0\\
-x^2>-7\\
x^2<7\\
(-1;\sqrt{7})\\
" alt="y=\frac{ln(7-x^2)}{x+1}\\
\\
x+1>0\\
x>-1\\
7-x^2>0\\
-x^2>-7\\
x^2<7\\
(-1;\sqrt{7})\\
" align="absmiddle" class="latex-formula"> сумма 1+2=3
![image](https://tex.z-dn.net/?f=9x%5E2-6x-1%3E0%5C%5C%0AD%3D36%2B4%2A1%2A9+%3D++6%5Csqrt%7B2%7D%5C%5C%0Ax_%7B1%7D%3D%5Cfrac%7B1%2B%5Csqrt%7B2%7D%7D%7B3%7D%5C%5C%0Ax_%7B2%7D%3D%5Cfrac%7B1-%5Csqrt%7B2%7D%7D%7B3%7D%5C%5C%0A%28-oo%3B%5Cfrac%7B1-%5Csqrt%7B2%7D%7D%7B3%7D%29+U++%28%5Cfrac%7B1%2B%5Csqrt%7B2%7D%7D%7B3%7D%3B%2Boo%29)
0\\
D=36+4*1*9 = 6\sqrt{2}\\
x_{1}=\frac{1+\sqrt{2}}{3}\\
x_{2}=\frac{1-\sqrt{2}}{3}\\
(-oo;\frac{1-\sqrt{2}}{3}) U (\frac{1+\sqrt{2}}{3};+oo)" alt="9x^2-6x-1>0\\
D=36+4*1*9 = 6\sqrt{2}\\
x_{1}=\frac{1+\sqrt{2}}{3}\\
x_{2}=\frac{1-\sqrt{2}}{3}\\
(-oo;\frac{1-\sqrt{2}}{3}) U (\frac{1+\sqrt{2}}{3};+oo)" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=2%5E%7B3-6x%7D%3E1%5C%5C%0A3-6x%3E0%5C%5C%0A-6x%3E-3%5C%5C%0A+x%3C%5Cfrac%7B1%7D%7B2%7D%5C%5C%0A+)
1\\
3-6x>0\\
-6x>-3\\
x<\frac{1}{2}\\
" alt="2^{3-6x}>1\\
3-6x>0\\
-6x>-3\\
x<\frac{1}{2}\\
" align="absmiddle" class="latex-formula">
очевидно что это -1